KESIAPAN MENIKAH PADA PEREMPUAN YANG MELAKUKAN PROSES TA’ARUF MENGGUNAKAN MODIFIKASI INVENTORI KESIAPAN MENIKAH-TEXT REVISED” - Shinta Mayasari (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
Adult people interested to have a marriage relationship. Marriage functions as a social control and a system which enable person to fulfill their needs, such as psychological, sexual, having children, and material (Papalia, Olds, Feldman, 2001). Marriage that can not fulfill such functions makes couple having a conflict and perhaps divorcement. Marriage readiness becomes a crucial factor to build a qualified marriage. Marriage readiness is the ability of a person to take their new roles, as a husband or wife.One of a process to step on marriage is called ta’aruf. The terms ta’aruf is an Arabic Language meaning knowing each other. In this field, ta’aruf is using as a reciprocal communication to knowing each other due to marriage (Hidayat, 2002). In ta’aruf, the couple can meet accompanying with someone they both can trust. Another way is using a media such as telephone or internet. Then they can continue their relationship seriously but still with accompanying of the third party. This is a quantitative field using questionnaire, interview, and observation method. The questionnaire is using MIKM-Text Revised consists of 76 items which measures eight domains. The participant is a young adulthood women which still doing a ta’aruf process and will marry for the first time in the next six months. The purpose of the field is to test the validity and the reliability of MIKM-TR, picturing of marriage readiness women doing ta’aruf process, and deeply interview their marriage readiness personally.Keywords: marriage readiness, ta’aruf process, women.